Risk of diabetes mellitus associated with disease-modifying antirheumatic drugs and statins in rheumatoid arthritis - (:unkn) unknown (BMJ PUBLISHING GROUP, 2017)
Objective To investigate the rate of incident diabetes mellitus (DM) in patients with rheumatoid arthritis (RA) and the impact of disease-modifying antirheumatic drug (DMARD) and statin treatments. Methods We studied patients with RA and >= 1 year participation in the National Data Bank for Rheumatic Diseases without baseline DM from 2000 through 2014. DM was determined by self-report or initiating DM medication. DMARDs were categorised into four mutually exclusive groups: (1) methotrexate monotherapy (reference); (2) any abatacept with or without synthetic DMARDs (3) any other DMARDs with methotrexate; (4) all other DMARDs without methotrexate; along with separate statin, glucocorticoid and hydroxychloroquine (yes/ no) variables. Time-varying Cox proportional hazard models were used to adjust for age, sex, socioeconomic status, comorbidities, body mass index and RA severity measures. Results During a median (IQR) 4.6 (2.5-8.8) years of follow-up in 13 669 patients with RA, 1139 incident DM cases were observed. The standardised incidence ratio (95% CI) of DM in patients with RA (1.37, (1.29 to 1.45)) was increased compared with US adult population. Adjusted HR (95% CI) for DM were 0.67 (0.57 to 0.80) for hydroxychloroquine, 0.52 (0.31 to 0.89) for abatacept (compared with methotrexate monotherapy), 1.31 (1.15 to 1.49) for glucocorticoids and 1.56 (1.36 to 1.78) for statins. Other synthetic/biological DMARDs were not associated with any risk change. Concomitant use of glucocorticoids did not alter DM risk reduction with hydroxychloroquine (HR 0.69 (0.51 to 0.93)). Conclusions In RA, incidence of DM is increased. Hydroxychloroquine and abatacept were associated with decreased risk of DM, and glucocorticoids and statins with increased risk.
Keywords: SYSTEMIC-LUPUS-ERYTHEMATOSUS; INFLAMMATORY JOINT DISEASES; PLACEBO-CONTROLLED TRIAL; POPULATION-BASED COHORT; INSULIN SENSITIVITY; ANKYLOSING-SPONDYLITIS; PSORIATIC-ARTHRITIS; DOUBLE-BLIND; HYDROXYCHLOROQUINE; THERAPY